Standarisasi Pernikahan Bagi Perempuan Suku Ammatoa di Kabupaten Bulukumba: Analisis Mazhab Fikih dan Hukum Adat - Sutriani, Sutriani; Ramli, Arif Rahman (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to analyze the comparison between the Shafi’I school and customary marriage law for women of the Kajang tribe (Ammatoa). So the objectives to be achieved in this study are: 1) to find out the form of standardization of marriage for women of the Kajang tribe (Ammatoa). 2) to find out the views between customary law and the Shafi’i school of thought regarding standardization of marriage for women of the Kajang tribe (Ammatoa). This research is classifield as a type of qualitative research and uses a shari’I, social and anthropological research approach. Types and sources of data in this study are primary data and secondary data with data collection methods used namely interviews, observasion, documentation and literature study. The results of this study indicate that there is pluralism in marriage law for the Kajang people, namely customary law, islamic law (shafi’I school) and positive law. However, what is interesting is that they prioritize customary law in their marriage procession after customary law has been implemented, then it fulfills the requirements as islamic law and positive law regulate regarding marriage. Then in the customary law that applies there is a prohibition on marrying other tribes, this is a must for every Kajang tribal community (Ilalang Emboya), for those who violate it will be subject to customary sanctions, namely they can be expelled from the customary area of the Kajang tribe area (Ammatoa).